2014
DOI: 10.1186/2052-9538-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-specific effects on weight loss outcomes in a comparison of sleeve gastrectomy and Roux-en-Y gastric bypass: a retrospective cohort study

Abstract: BackgroundRoux-en-Y gastric bypass (RYGBP) and sleeve gastrectomy (SG) are the most common bariatric procedures undertaken globally but there are no evidenced-based criteria that inform the selection of one operation over the other. The purpose of this study was thus to compare weight loss outcomes between RYGBP and SG, and to define patient factors affecting weight loss.MethodsA single-centre two-year follow-up retrospective cohort study of all adults who underwent either RYGBP (n = 422) or SG (n = 432) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Both types of bariatric operations lead to significant weight loss, but the superiority of one type over another is disputable. Manning et al reported better weight loss after RYGB [17]. However, in our study, the difference between %EWL at each follow-up was not significant.…”
Section: Discussioncontrasting
confidence: 88%
“…Both types of bariatric operations lead to significant weight loss, but the superiority of one type over another is disputable. Manning et al reported better weight loss after RYGB [17]. However, in our study, the difference between %EWL at each follow-up was not significant.…”
Section: Discussioncontrasting
confidence: 88%
“…We found that patients with DDBS lost on average 4.1 kg less of absolute weight than those without DDBS and the BMI variation was also 1.4 kg/m 2 less than those without DDBS. It is known, however, that there are some variables that may interfere with the outcomes of weight variation after BS [12][13][14]. After adjustment for sex, age, and BS type, this effect was maintained.…”
Section: Discussionmentioning
confidence: 97%
“…There was little difference between the procedures for other factors. Most other studies have suggested that sleeve gastrectomy may be safer than gastric bypass [ 23 – 27 ], though some found no relevant differences [ 28 ]. These findings suggest that adverse outcomes after bariatric surgery are rare, hospital stays are short, and the benefits we report here outweigh the short-term risks involved.…”
Section: Discussionmentioning
confidence: 99%